Vlog Content and YouTuber Image on the Decision to Donate with Awareness of Donating as an Intervening Variable - Roli Apriyansyah; Sisnuhadi Sisnuhadi (Universitas Proklamasi 45, 2022)
The development of information technology impacts the pattern of society in collecting social funds. One of the popular technologies used in social fundraising efforts is YouTube. This research is in the form of field research which aims to analyze the effect of vlog content and YouTuber image on the decision to donate with the awareness of donating as an intervening variable. This study uses quantitative methods. Sources of data were obtained through research questionnaires which were distributed directly. A total of 110 questionnaires were successfully collected. Funds were analyzed using a variant-based structural equation model (SEM) analysis, known as Partial Least Square (PLS). The results of data analysis prove that vlog content, and YouTuber imagery have a significant influence on awareness of donation. This research also confirms that the vlog content and YouTube image affect the decision to donate through awareness to donate. Furthermore, awareness of donating is proven to significantly influence the decision to donate.